An unusual surgical complication: Slipped molar lodged in vocal cords and its anesthetic management - Ameerunnisha begum; Ramsesh Manohar Ram; Monisha Prasad (Journal of Oral Biology and Craniofacial Research)
Background: Extraction of wisdom tooth is one of the most common surgical interventions, as it is more prone for impaction. Due to the pain and anxiety associated with the procedure, it is common to do this procedure under conscious sedation. However unexpected events do occur during the procedure and one such complication along with the prompt management is discussed here. Case report: This case report details an unusual occurrence of a third molar tooth slipping during dental extraction and becoming lodged at the base of the vocal cords. The patient, a 52-year-old man with a history of hypertension, underwent the procedure under conscious sedation. The case report highlights the importance of preparedness and multidisciplinary coordination in managing rare complications during dental procedures under conscious sedation. The accidental aspiration of a molar tooth into the airway required prompt and effective intervention, using dexmedetomidine for sedation, fibre-optic bronchoscopy for visualization, and a range of retrieval instruments. Using video-assisted laryngoscopy and fibre-optic laryngoscopy proved indispensable in locating and safely retrieving the foreign body without resorting to more invasive procedures. Conclusion: This case highlights the importance of anaesthesiologist's role in emergency management and comprehensive preparedness in dental practice.